Dinamika Kependudukan dan Ketenagakerjaan: Tantangan dan Kebijakan Berkelanjutan untuk Indonesia - Sagara, Robi; Setiawan, Ahmad Hapsak; Almuzafir; Purnawan, Endar (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study examines population dynamics and employment in Indonesia, along with the challenges in formulating sustainable policies. Using a qualitative method with a literature review approach, this research analyzes various documents from BPS, Bappenas, previous studies, and other sources that explore population and employment issues. The findings indicate that Indonesia needs to strengthen investment in vocational education, develop sustainable urbanization policies, and encourage the transition of the informal sector to the formal economy. Additionally, creating elderly-friendly cities and expanding social security are essential to improving societal well-being. The success of these policies largely depends on the synergy between the government, the private sector, and civil society in fostering inclusive development programs. This study contributes to policy recommendations for addressing population and employment challenges in Indonesia. However, its limitation lies in the general scope of data, suggesting that future research should conduct empirical studies based on regional data to assess policy effectiveness more specifically.